2013
DOI: 10.1007/s00246-013-0666-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Extracorporeal Membrane Oxygenation for Pediatric Cardiac Arrest in the United States: Analysis of the Kids’ Inpatient Database

Abstract: To characterize the overall use, cost, and outcomes of extracorporeal membrane oxygenation (ECMO) as an adjunct to cardiopulmonary resuscitation (CPR) among hospitalized infants and children in the United States, retrospective analysis of the 2000, 2003, and 2006 Kids' Inpatient Database (KID) was performed. All CPR episodes were identified; E-CPR was defined as ECMO used on the same day as CPR. Channeling bias was decreased by developing propensity scores representing the likelihood of requiring E-CPR. Univar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 47 publications
0
35
1
2
Order By: Relevance
“…(70)(71)(72)(73) ECMO, however, was associated with increased complications (e.g. haemorrhage, thrombotic events) and was more resource-intensive.…”
Section: Ecmo In Cpr and Paediatric Ihcamentioning
confidence: 99%
See 1 more Smart Citation
“…(70)(71)(72)(73) ECMO, however, was associated with increased complications (e.g. haemorrhage, thrombotic events) and was more resource-intensive.…”
Section: Ecmo In Cpr and Paediatric Ihcamentioning
confidence: 99%
“…haemorrhage, thrombotic events) and was more resource-intensive. (70) In a retrospective review of a paediatric IHCA registry database, ECPR was shown to improve survival in patients with isolated cardiac disease when CPR alone had failed, especially in surgical cardiac patients. (68,70) The majority of survivors who received ECPR had a favourable neurological outcome.…”
Section: Ecmo In Cpr and Paediatric Ihcamentioning
confidence: 99%
“…For the critical outcome of survival to hospital discharge, we identified very-low-quality evidence from 4 pediatric observational studies of IHCA [71][72][73][74] (downgraded for indirectness, inconsistency, and residual confounding) and very-low-quality evidence from 1 unpublished analysis of a study' s public dataset 75 (downgraded for serious risk of residual confounding) showing no benefit to the use of ECPR when compared with CPR without the use of ECMO (RR range, 0.64-1.63). We also identified low-quality evidence (downgraded for indirectness, inconsistency, and residual confounding) from a single pediatric study of IHCA 76 that showed benefit to ECPR when compared with CPR without the use of ECMO (OR, 2.5; 95% CI, 1.3-4.5; P50.007 in surgical cardiac diagnoses; OR, 3.8; 95% CI, 1.4-5.8; P50.011 in medical cardiac diagnoses).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…This therapy may be associated with added complications for individual patients (eg, hemorrhage) and significant costs for a healthcare system. 71 The motivation to examine this topic was to provide guidance on the use of ECMO when used with conventional resuscitation measures for the purpose of optimizing survival, recovery, and neurologic outcome from pediatric IHCA. This review did not evaluate the use of ECPR for the purpose of supporting a patient for the end point of organ donation for transplantation as this may involve different resuscitation goals and targets.…”
Section: Introductionmentioning
confidence: 99%
“…40 Median hospital charges of ECPR patients has been quoted at $310824, which is significantly greater than charges for propensity-matched conventional CPR patients, which are $147817. 42 Financial burdens of ECMO support may far exceed reimbursement from insurance companies and may place the hospital at financial risk. 40,43 Offering excess treatment in one patient may conceivably lead to a decrease in resources for another patient.…”
Section: Ethical Considerationsmentioning
confidence: 99%